2019
DOI: 10.1186/s12886-019-1072-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of choroidal parameters in eyes at the first onset of acute anterior uveitis

Abstract: Background Little is known about choroidal involvement in anterior uveitis. The aim of our study was to evaluate changes in choroidal thickness and volume in eyes with acute anterior uveitis (AAU) using enhanced depth imaging-optical coherence tomography (EDI-OCT) at baseline and after treatment, which were compared with healthy fellow eyes. Methods For the study, 35 individuals with unilateral acute AAU at the first onset were enrolled. Subfoveal thickness and choroida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Попытки оценить роль этого параметра при передних увеитах [7][8][9][10][11][12][13][14] дали противоречивые результаты. В ряде работ обнаружено увеличение толщины сосудистой оболочки в субфовеолярной и парафовеолярной зонах в период активности воспаления [8,10,[12][13][14], а H. Yan и соавт.…”
unclassified
“…Попытки оценить роль этого параметра при передних увеитах [7][8][9][10][11][12][13][14] дали противоречивые результаты. В ряде работ обнаружено увеличение толщины сосудистой оболочки в субфовеолярной и парафовеолярной зонах в период активности воспаления [8,10,[12][13][14], а H. Yan и соавт.…”
unclassified
“…Although by definition, anterior uveitis (AU) denotes involvement of the anterior segment of the eye, a limited number of studies have also reported changes in the CT in patients with acute anterior uveitis (AAU) suggesting possible choroidal involvement in AU. [ 1 2 3 4 5 6 7 8 9 10 ] Recent advances in spectral-domain optical coherence tomography (SD-OCT) with enhanced depth imaging (EDI) mode and swept-source OCT (SS-OCT) have led to better imaging of the choroid providing further insight to pathogenesis of such entities.…”
mentioning
confidence: 99%
“…Majority of the studies assessing CT in AAU have evaluated unilateral nongranulomatous AAU or selective HLA-B27-associated AAU patients and compared the CT with either healthy fellow eye or a separate group of age-matched healthy control additionally. [ 1 2 3 4 6 7 8 9 ] Few of these studies are retrospective,[ 1 3 7 8 ] while others are prospective;[ 2 4 5 6 9 ] the sample size varied between 16 and 120 patients of AAU across these studies. [ 1 2 3 4 5 6 7 8 9 ] Measurement of the CT in these studies was derived either from single point subfoveal CT or from multiple Early treatment of Diabetic Retinopathy Study (ETDRS) subfields with the help of in-built caliper-based manual measurement or automated integrated software-based segmentation of the sclero-choroidal interface (SCI).…”
mentioning
confidence: 99%
See 2 more Smart Citations